Effektivitas Penerapan Kolam Detensi dan Sistem Pompa dalam Pengendalian Banjir di Kampung Rawa Bamban - Fuad Hasan; Bambang Eko Widyanto (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
Kampung Rawa Bamban, Benda District, Tangerang City, is highly prone to flooding due to its flat topography, inadequate drainage systems, and uncontrolled water flow. High rainfall intensifies the issue, leading to prolonged inundation. Flooding results in significant material losses, disrupts daily activities, and degrades environmental quality. Therefore, an effective and sustainable solution is essential. This study aims to evaluate the effectiveness of detention ponds and pump systems as an integrated flood control strategy. The research employs topographic analysis, flood volume calculations, and hydrologic-hydraulic simulations to assess the performance of retention ponds and pumps. The detention pond functions as a temporary reservoir for stormwater runoff, while the pump discharge excess water into drainage channels once the pond reaches its capacity. The results show that the retention pond can store up to 1,208 m³ of stormwater. Based on land availability, the pond is designed with a surface area of 300 m² and a depth of 4 m, supported by a pump with a capacity of 300-liters-per-second. Model simulations indicate that the pond reaches near-maximum elevation at 05:36, prompting triggering pump activation at 05:37. After operating for approximately two hours, the pond is fully drained before 07:00. The combination of detention pond and pump is effective in reducing the flood extent and shortening the inundation duration. This study offers valuable insights for local governments in developing sustainable flood mitigation strategies.